Quality of Life Among Elderly People in Chitwan District, Nepal - Poudyal, Jiwan Kumar; Shakya, Dhanendra Veer; Parajuli, Sumitra; Dhungana, Govinda Prasad (BMC Journal of Scientific Research, 2023)
As the world's elderly population grows, the Quality of Life (QoL) of the elderly becomes an emerging issue and plays a vital role in social development. The aim of this study was to assess the QoL of elderly people in the Chitwan district, Nepal. An analytical cross-sectional study design was employed to evaluate the Quality of Life (QoL) among the elderly residing in the 17 wards encompassing all municipalities and the metropolitan area. The sampling method employed was Probability Proportionate to Size (PPS), which facilitated the selection of 26 respondents from each of the chosen wards. In total, 442 elderly individuals were recruited from the community and surveyed using the WHOQoL-brief questionnaire. Descriptive and inferential statistics were used to analyze data in SPSS 20. Most of the elderly mentioned neutral status in both overall QoL (71%) and satisfied with their health status (48.4%). Elderly aged 60-69 years had higher QoL scores in the physical (p